Headache attributed to giant cell arteritis complicated with rheumatic polymyalgia diagnosed with F18-fluorodeoxyglucose positron emission tomography and computed tomography: a case report - Wang, Dong; Liu, Zunjing; Guo, Huailian; Yang, Li; Zhang, Xinhua; Peng, Li; Cheng, Min; Jiang, Hong (Frontiers in Neurology, 2023)
Giant cell arteritis (GCA) is a kind of systemic vasculitis affecting individuals over 50 years old and is often the cause of new-onset headaches in older adults. Patients with GCA sometimes have rheumatic polymyalgia (PMR). The diagnosis of GCA generally depends on clinical manifestation, elevated erythrocyte sedimentation rate (ESR) or C-reactive protein, and positive imaging findings commonly obtained by ultrasound or temporal artery biopsy. In this study, we report a case of an 83-year-old woman with a new-onset headache and an elevated ESR. The result of the temporal artery ultrasound did not distinguish between vasculitis and atherosclerosis. The F18-fluorodeoxyglucose positron emission tomography and computed tomography (18F FDG PET-CT) were performed and suggested large vessel vasculitis with temporal artery involvement. In addition, polyarticular synovitis and bursitis were also revealed. Finally, the diagnosis of secondary headache attributed to CGA complicated with PMR was established. The patient experienced remission of symptoms after glucocorticoid therapy. PET can become a powerful tool for diagnosis and differential diagnosis when the ultrasound result is ambiguous and a biopsy is not obtained.